THE CONSTRUCTION OF MEN MASCULINE BODY - Budyati, Laily Eros; M.Si, Hapsari Dwiningtyas; ., Nuriyatul laililaya; ., Triyono Lukmantoro (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The mass media often show about the social construction of masculine and feminine developed in the society become a reality. The mass media including magazines usually use discourses which relate to the body construction to maintain the values of the masculine and feminine. Men's Health Indonesia magazine seems to use sport and health discourse that is used to form the construction of men masculine body. The purpose of this study is to reveal how the men masculine body is constructed by the sport and health discourse in the Men's Health Indonesia magazine and reveal marginalized group. This study use a qualitative approach with Roland Barthes’ semiotic analysis through the staggered system of denotation and connotation. This research is supported by the Hegemonic Masculinity Theory by Robert William Connell and Disciplining Body Theory by Michel Foucault.. The results of this study indicate that the Men's Health Indonesia magazine still maintain masculinity value. Men's Health Indonesia magazine constructs men masculine body as mesomorph. Mesomorphic shape is one that is athletic and muscular with wide shoulders and chest which taper to a comparatively narrower waist, they often have a powerful posture as well. Masculinity values also relate to the modification of the men body through tattoos, masculine appearance, modification of men body building through exercise fitness, heterosexual and active position in the romantic relationship, and this ideal and healthy body can be shaped by a balanced diet and nutrition. Men masculine body is disciplined by the discourse of sport and health so this discourse becomes a truth, normality, and considered to be the knowledge that is predominantly used to control the men body in order to become a docile body and eliminate the knowledge that is not deemed the standards of an ideal and healthy body. Masculinity in the magazine tend to follow hegemonic masculinity that puts the dominant position of men and women's subordination. Besides women, hegemonic masculinity also marginalized certain groups of men who can not fulfill the ideal criteria.